How does interface influence the level of analgesia when Virtual Reality distraction is used? - Piskorz, Joanna; Czub, Marcin; Urbańska, Katarzyna (psycholog); Mrula, Małgorzata; Hodowaniec, Paweł; Misiewicz, Mateusz (Department of Psychology, University of Wrocław, 2014)
This study investigates the effectiveness of virtual reality (VR) technology in distracting attention from pain. We tested how body engagement related to navigating the virtual environment (VE) influences the intensity of pain. Two different interfaces were used to play the same VE, and a cold pressor test was used for pain stimulation. A mixed design was used for the experiment. Sixty-six undergraduate students participated. One group navigated the game using a rotation sensor, head tracker and foot pedals (Body Movement Interface). Another group navigated only using their hands (Hand Movement Interface). Objective and subjective measures of pain were collected – the amount of time participants kept their hand in a container with cold water, and the participant’s assessment of the pain intensity on a visual analog scale (VAS). Participants also filled in questionnaires designed to measure feelings of presence in VE and emotional attitudes towards the game. We found no significant difference between the two used interfaces in their analgesic efficacy. In both groups during VR distraction, participants showed significantly higher levels of pain endurance than without VR distraction.
Keywords: pain tolerance; thermal stimulation; analgesia; virtual reality; virtual environment